Daniel's triple challenge

Algebra Level 5

How many ordered triples of complex numbers ( a , b , c ) (a, b, c) are there such that a 3 b a^3-b , b 3 c b^3-c , and c 3 a c^3-a are rational numbers, and

a 2 ( a 4 + 1 ) + b 2 ( b 4 + 1 ) + c 2 ( c 4 + 1 ) = 2 ( a 3 b + b 3 c + c 3 a ) ? a^2(a^4+1)+b^2(b^4+1)+c^2(c^4+1)=2(a^3b+b^3c+c^3a)?

This problem is posed by Daniel C .


The answer is 27.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

3 solutions

Mark Hennings
Oct 8, 2013

The equation becomes ( a 3 b ) 2 + ( b 3 c ) 2 + ( c 3 a ) 2 = 0 (a^3-b)^2 + (b^3-c)^2 + (c^3-a)^2 \; = \; 0 so we deduce that b = a 3 b = a^3 , c = b 3 c = b^3 and a = c 3 a = c^3 . Thus a 27 = a a^{27} = a , and hence either a a is 0 0 (in which case a = b = c = 0 a=b=c=0 or else a a is one of the twenty-six 26 26 th roots of unity (in which case b = a 3 b=a^3 and c = a 9 c=a^9 . There are 27 27 different values for a a , which then determine the values for b b and c c . Thus there are 27 27 ordered triples.

Moderator note:

Brilliant observation!

Out of curiosity, what made you think of the equation? Once we have that, the rest become very direct.

Calvin Lin Staff - 7 years, 8 months ago

Log in to reply

Problems like this often resolve to a "a sum of squares is zero, so all the summands are zero" argument. When I saw terms like a 6 a^6 and 2 a 3 b 2a^3b in the equation, completing the square seemed a good bet to try,

Mark Hennings - 7 years, 8 months ago

Wow didnt expect this amazing result to this problem.

Dinesh Chavan - 7 years, 8 months ago
Daniel Chiu
Oct 6, 2013

First, we move all terms to one side and expand: a 6 + a 2 + b 6 + b 2 + c 6 + c 2 2 a 3 b 2 b 3 c 2 c 3 a = 0 a^6+a^2+b^6+b^2+c^6+c^2-2a^3b-2b^3c-2c^3a=0 Now, seeing the rational condition, we might wonder what is has to do with the problem, and with a little bit of looking at our equation, it isn't hard to see the factorization: ( a 3 b ) 2 + ( b 3 c ) 2 + ( c 3 a ) 2 = 0 (a^3-b)^2+(b^3-c)^2+(c^3-a)^2=0 Now, since all three squares are rational and positive, they must all be 0. We have three equations: a = c 3 a=c^3 c = b 3 c=b^3 b = a 3 b=a^3 Clearly, one solution is ( a , b , c ) = ( 0 , 0 , 0 ) (a,b,c)=(0,0,0) . We can substitute: a = c 3 = ( b 3 ) 3 = ( ( a 3 ) 3 ) 3 = a 27 a=c^3=(b^3)^3=((a^3)^3)^3=a^{27} If a 0 a\neq 0 , we can divide by a a , giving: a 26 = 1 a^{26}=1 Therefore, a a is a 26th root of unity, and similarly, so are b b and c c . Let a = e i n π 13 a=e^{i\dfrac{n\pi}{13}} Therefore, using our equations: b = e i 3 n π 13 b=e^{i\dfrac{3n\pi}{13}} c = e i 9 n π 13 c=e^{i\dfrac{9n\pi}{13}} a = e i 27 n π 13 a=e^{i\dfrac{27n\pi}{13}} Since e i x e^{ix} is periodic with period 2 π 2\pi : a = e i 27 n π 13 = e i n π 13 a=e^{i\dfrac{27n\pi}{13}}=e^{i\dfrac{n\pi}{13}} Therefore, every 26th root of unity satisfies our equation, and gives one triple ( a , b , c ) (a,b,c) , and so the answer is 27 \boxed{27} .

Your solution is hard to understand..

Master Mind - 7 years, 7 months ago
Ton de Moree
Oct 12, 2013

Noticing that the squares of the given rational numbers resemble the parts in the equation, the equation can be rewritten as:

a 6 2 a 3 b + b 2 + b 6 2 b 3 c + c 2 + c 6 2 c 3 a + a 2 = 0 a^6-2a^3b+b^2 + b^6-2b^3c+c^2 + c^6-2c^3a+a^2 =0

( a 3 b ) 2 + ( b 3 c ) 2 + ( c 3 a ) 2 = 0 (a^3-b)^2+(b^3-c)^2+(c^3-a)^2=0

As squares of rational number are always greater than or equal to 0 0 , it follows that;

a 3 = b a^3=b , b 3 = c b^3=c and c 3 = a c^3=a .

Substituting in eachother gives us that a 27 = a a^{27}=a , so either a = 0 a=0 or a = e 2 n π i 26 a=e^{\frac{2n \pi i}{26}} ( 0 n 25 0 \le n \le 25 ).

So there are 27 27 ordered triplets satisfying the given.

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...